Analysis of CTLA-4 (+49A/G) Gene Polymorphism and the Risk of Pulmonary Tuberculosis in Babylon province of Iraq - Raafat M. AL- Enzi1, Jawad Kadhim Tarrad1, Moshtak A. Wtwt1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Pulmonary tuberculosis (pTB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis (M. tuberculosis). It typically affects the lungs, but can also affect other sites (extra- pulmonary TB). The disease is spread when sick individuals expel bacteria into the air, for example by coughing.Aim of Study: To highlight the effect of CTLA-4 (+49A/G) gene polymorphism on the risk of pulmonary Tuberculosis (pTB).Patients and Methods: This case-controlled study used single specific primer-polymerase chain reaction (SSP-PCR) to analyze the CTLA-4 (+49A/G) gene polymorphism in 60 patients with pTB who were referred to consultant clinic for respiratory diseases in Hilla – Babylon province/ Iraq during the period from December 2017 to July 2018, and 60 healthy persons’ control. Blood samples were collected from both groups according to the standard methods.Results: Data analysis revealed that the frequencies of AA, AG and GG genotypes in patients were 73.33%, 23.33%, and 3.34% respectively. In controls, this frequency was 51.67%, 35%, and 13.33% respectively. Logistic regression test detected a significant difference in the frequency of the (GG genotype) mutant homozygous of this polymorphism between patients and controls (3.34% versus 13.33%), The GG genotype of CTLA-4(+49A/G) showed a significantly decreased risk of pulmonary tuberculosis disease (OR= 0.18, 95% CI= 0.04 – 0.88, P value = 0.035).Conclusion: The GG genotype of CTLA-4 may decrease the risk of pTB.